Indigenous peoples and environmental management : a review of Canadian Regional Agreements and their potential application to Australia. Part 1. by Benjamin J. Richardson, Donna Craig, Ben Boer - Richardson, Benjamin J.; Craig, Donna.; Boer, Ben. (1994)
tag=1 data=Indigenous peoples and environmental management : a review of Canadian Regional Agreements and their potential application to Australia. Part 1. by Benjamin J. Richardson, Donna Craig, Ben Boer tag=2 data=Richardson, Benjamin J.%Craig, Donna%Boer, Ben tag=3 data=Environmental and Planning Law Journal, tag=4 data=11 tag=5 data=4 tag=6 data=August 1994 tag=7 data=321-343. tag=8 data=ABORIGINESORIGINAL LAND CLAIMS%ENVIRONMENT tag=9 data=NATIVE TITLE ACT tag=10 data=This article reviews and analyses the history of regional agreements in Canada, in particular the James Bay and Northern Quebec Agreement and the Yukon Agreement. Provided by MICAH, Canberra. tag=11 data=1994/6/9 tag=12 data=94/0552 tag=13 data=CAB This article reviews and analyses the history of regional agreements in Canada, in particular the James Bay and Northern Quebec Agreement and the Yukon Agreement. Provided by MICAH, Canberra.